"She has promised never to use the N-word again": Discourses of racism in a Swedish media debate. (October 2019) - Idevall Hagren, Karin
Abstract: In Sweden, as in most European countries, antiracist discourses co-exist with new racism and right-wing populism. Self-images as antiracist are maintained through the strategy to deny racism and accusations of racism. This article addresses discourses of racism in a Swedish media debate that started with a YouTuber being accused of using the N-word. Through a categorization analysis of newspaper articles, that report on and debate the incident, the management of accusations and denials, as well as language ideologies and different perspectives on racism, are examined. The analysis shows how the YouTuber, and journalists, deny racism by claiming that the racist expression was an unintentional "gaffe", thus categorizing the YouTuber as a non-racist. This understanding of racism, as an individual and intentional phenomenon, dominates the debate. However, some debaters advocate a structural discourse of racism, focusing on racist activities rather than racist individuals. Nevertheless, the findings suggest that the media context does not provide room for a nuanced discussion about structural racism and racist language. Instead, the category work indicates that the maintenance of social relations and an antiracist self-image is the core activity of the interaction.